Innovation cycles and productivity gain in the maritime transport (propulsion) - Tang, Edmund Lek Weng (2018)
Marine propulsive innovations have been evolving continually since primitive days, with each innovation disrupting the former in a shorter span of time while yielding incremental benefits. The area of discussion in propulsive innovation revolves around engines, propellers and rudders which are key components responsible for vessel propulsion and navigation. Their benefits were often qualitative subjects of increased efficiency by reducing fuel consumption and increasing horsepower generation, reduced emission levels and shorter voyage time. However, this form of expression lacks elaboration and justification as it fails to portray the extent of exponential growth in each innovation with time. Hence, this report has quantified the productivity gains for each innovation in monetary form while drawing a relation with its predecessor to visualize and compare the extent of improvement from past, present and into the future. By far, historical studies have measured productivity gains of propulsive innovation using only freight rates. As such, the author has sought other mediums of measurement for instance, savings on fuel costs and time charter hire or earnings from cargo space saved, for analytical comparison. Concluding results demanded a need for further technical research on cleaner engines that possess equal or better thermal efficiency than diesel engines, hybrid solutions, azimuth thrusters and its material as well as incorporation of block chain technology in vessel propulsion.